Vibration based energy harvesting using piezoelectric material - Mohd Kazim, Mohd Nor Fakhzan; Abdul Muthalif, Asan Gani (2011)
Energy harvesting has been around for centuries in the form of windmills, watermills and passive solar power systems. It is not only restricted to the natural resources but it has widen the tapping source to utilise the vibration which happen all around us. In the last decade, beam with piezoceramic patches have been used as a method to harverst energy. An energy harvester system modelled in this paper consist of unimorph piezoelectic cantilever beam with a tip mass. It generates electric current or voltage from the piezoelectric strain effect due to base excitation. This paper is aimed at developing a mathematical model of unimorph cantilever beam with piezoelectric harvester by using Euler– Bernoulli beam theory. The step by step analytical solution and the simulation result are shown in the form of voltage around the natural frequencies.